Strategies of Visionary Islamic Leadership in Achieving Success at Junior High School Education Institution in Central Lombok - Marianto, Jas Adi; Citriadin, Yudin; Hardi, Lalu Mohamad Zaki; Fauziah, Nurul (Research, Training and Philanthropy Institution Natural Aceh, 2025)
This research aims to determine Islamic visionary leadership strategies in successfully leading junior high school educational institutions in Central Lombok. This research employs a qualitative approach, utilizing a case study design. Research informants are school principals, teachers, and other stakeholders. Data collection uses observation, interviews, and documentation. Data analysis with stages of data presentation, data condensation, and conclusion. Checking the validity of data with consistency, objectivity, and transferability. The research results indicate that Islamic visionary leadership fosters an educational climate that upholds the core values of justice, trust, and deliberation. Apart from that, strengthening leadership capacity and collaboration between stakeholders is a strategic factor in enhancing the existence of Islamic educational institutions. The research implication is that Islamic visionary leadership not only manages educational administration but also builds an integrated vision of scientific excellence and moral-spiritual values. The application of this principle has a positive impact in various aspects: (1) Producing graduates who are intelligent and have noble character, (2) Making Islamic values basic in education policy, (3) Building a work culture that strategically respects teachers and staff, (4) Producing graduates who are competent, honest, responsible and have a leadership spirit, (5) Making educational institutions a center for da'wah and social empowerment.